(untitled) (Texas Journal of Engineering and Technology, 2022)
The development of scientific and technical progress led to the emergence of electronic tools and their active introduction into various spheres of society. Their use has become an integral part of social, economic, political and educational spheres. Higher education institutions are actively using these funds to train highly qualified specialists. Information and communication technologies are a tool that helps to form the professional competence of students. The article examines the issue of integrating modern pedagogical and information and communication technologies, including electronic tools, at the university.